Influence of processed neem fruit and yeast mixtures on performance and digestibility of West African Dwarf sheep (2016)
A feeding trial using sixteen (16) male West African Dwarf (WAD) sheep with an initial live weight of 14.41±2.54kg was conducted to determine the effect of processed neem fruit and yeast supplementation on their performance characteristics and nutrient digestibility. The rams were assigned to four dietary treatments of four rams per treatment consisting of control (T1), yeast alone at 5 g/d (T2), neem fruit alone at 5 g/d (T3) and yeast plus neem fruit at 5 g/d (T4). The dry matter (%) contents were 93.03, 93.04, 93.71 and 93.71 while the crude protein were 8.75%, 8.75%, 10.29% and 10.29% for diets 1, 2, 3 and 4 respectively. Feed at 5% body weight and water were offered in one radon a day. Daily feed intake and body weight changes were determined and feed efficiency calculated. On the 56th day, three rams per treatment were selected for metabolic study. Nutrients digestibility were calculated and computed while nitrogen retention study was determined. Results indicated that yeast and neem fruit supplementation generally improved intake and average daily weight gain in WAD sheep, Aho, DM (56.71, 57.19 and 69.16%) and ME (7.63, 7.47 and 8.05MJ/kgDM) digestibility for diets 2, 3 and 4 differed significantly (P<0.05) from diet 1 (DM 49.74% and M.E 5.55MJ/kgDM). Also, CP digestibility for diet 4 (82.73%) differed significantly (P<0.05) from diets 1, 2 and 3 (72.79, 76.79 and 76.33%) respectively. The DM intake (g/day) across the treatments differed significantly (P<0.05) with the best obtained from animals fed diet 4 (898.32g/d) and the least from animals fed diet 1 (636.06g/d). The best nitrogen retention was obtained from animals fed diet 4 and diet 1 gave the least Addition of yeast and processed neem fruit (T4) promoted average daily weight gain and performance was comparatively better than those on other diets.